ANALISIS PELAKSANAAN NILAI-NILAI TOLERANSI SOSIAL MAHASISWA DI ASRAMA PUTRA KAYONG II PONTIANAK - Afrian, Dodi; Bahari, Yohannes; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aims of this study are to find out (1) the implementation of accepting among students, (2) the implementation of respecting among students, (3) the implementation of appreciating among students in Putra Kayong II Dormitory. The data analysis in this study was presented in descriptive qualitative research by using four informants, consists of one chief and three residents of the dormitory who came from different ethnic. The technique of data collection in this study is conducted through observation, interview and documentation, while the tools of data collection being used are observation checklist, interview guideline and documentation tool. The results of this study prove that in Putra Kayong II Dormitory in terms of (1) Accepting new students, advice, and sharing also hanging out with anyone openly without exception, no discrimination, no arrogance, not offensive and unselfish. (2) Respecting each other students despite their different belief and ethnic respectfully, without prejudice, without reproach, and without discrimination. (3) Respecting opinions, critic and collective decision is accepted gracefully, without reproach, without emotional and acting wise in response. Keywords: Accepting, Appreciating, Respecting, Social Tolerance.